WORLD BANK LENDING FOR HIGHER EDUCATION AND RESEARCH: LESSONS AND IMPLICATIOM FOR EASTERN EUROPE - Eisemon, Thomas Owen (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1994)
World Bank strategies for reforming and rehabilitating higher education and research systems in Eastern Europe are examined in the context of its world-wide lending experience in higher education. Information is presented on the kinds and distribution of Bank higher education investments from 1963 to 1991. Attention is given to recent projects in Brazil, China, and Hungary that have significantly influenced the way the Bank has understood key issues involved in restructuring higher education and research systems in Eastern Europe. The importance of creating the right incentives for institutions and researchers is emphasized as well as the fragility of economic and political systems in the region. RÉSUMÉ Les stratégies de la Banque Mondiale au titre de la réforme et de la revalorisation de la recherche et de l'enseignement supérieur en Europe de l'Est sont examinées sous l'angle des prêts internationaux qu'elles concèdent dans le domaine de l'enseignement supérieur. Des données sont fournies sur la nature et la répartition des placements effectués par la Banque Mondiale dans l'enseignement supérieur entre 1963 et 1991. L'auteur centre son attention sur les projets récents au Brésil, en Chine et en Hongrie qui ont considérablement influencé la manière dont la Banque a saisi les problèmes clés liés à la restructuration de la recherche et de l'enseignement supérieur en Europe de l'Est. La nécessité de créer des mesures d'incitation appropriées pour les établissements et les chercheurs y est mise en valeur au même titre que lafragilité des systèmes politiques et économiques de cette région du globe.